Inhibition of non-canonical NF-κB signaling suppresses periodontal inflammation and bone loss - Aoki, Tsukasa; Hiura, Fumitaka; Li, Aonan; Yang, Nan; Takakura-Hino, Nana; Mukai, Satoru; Matsuda, Miho; Nishimura, Fusanori; Jimi, Eijiro (Frontiers in Immunology, 2023)
Periodontal disease is an infectious disease that affects many people worldwide. Disease progression destroys the alveolar bone and causes tooth loss. We have previously shown that alymphoplasia (aly/aly) mice harboring a loss-of-function mutation in the map3k14 gene, which is involved in p100 to p52 processing of the alternative NF-κB pathway, exhibited mild osteopetrosis due to decreased number of osteoclasts, suggesting the alternative NF-κB pathway as a potential drug target for the amelioration of bone disease. In the present study, wild-type (WT) and aly/aly mice were subjected to silk ligation to establish a periodontitis model. Alveolar bone resorption was suppressed in aly/aly mice by decreased numbers of osteoclasts in the alveolar bone in comparison to WT mice. Furthermore, the expression of receptor activator of NF-κB ligand (RANKL) and TNF (cytokines involved in osteoclast induction in periligative gingival tissue) was decreased. When primary osteoblasts (POBs) and bone marrow cells (BMCs) derived from WT and aly/aly mice were prepared and co-cultured, osteoclasts were induced from WT-derived BMCs, regardless of the origin of the POBs, but hardly formed from aly/aly mouse-derived BMCs. Furthermore, the local administration of an NIK inhibitor, Cpd33, inhibited osteoclast formation and thereby inhibited alveolar bone resorption in the periodontitis model. Therefore, the NIK-mediated NF-κB alternative pathway can be a therapeutic target for periodontal disease.